Investigation of technology use and need satisfaction levels of adolescents according to some variables - Kaba, İlker and Doğan, Türkan (Journal of Dependence, 2022)
Objective: The aim of this study was to determine whether the levels of adolescents’ use of information technologies and basic psychological needs differed by gender, and if so, what was the relation in between the duration and reasons of using information technologies. Method: The study was carried out with the screening model. Personal Information Form, Information Technologies Usage Scale (ITUS) and Need Satisfaction Scale (NSS) were used in the research. The data were collected from 508 adolescents in high schools in Ankara and Mersin provinces in the 2019-2020 academic year, using the convenience sampling method. Results: The mean scores derived from the factors of NSS-Efficacy, ITUS-Digital Gaming (DG) and ITUS-Use of Technological Devices and Applications (UTDA) differed significantly by gender. It was determined that the daily internet usage duration of the adolescents and the mean scores obtained from the ITUS-DG, ITUS-UTDA factors and the overall ITUS were positively and significantly correlated. Using the internet for playing games and the mean scores of ITUS-DG, ITUS-UTDA, ITUS-Virtual Life Preference factors and the overall ITUS were positively and significantly related to using the Internet for social networks and the mean scores obtained from the NSS-Relatedness factor and overall NSS. Conclusion: The direction of their relations with the general and subscales of ITUS, overall and subscales of NSS differs by gender, duration of use of information technologies and purposes of the adolescents. It was observed that the duration of information technology use has increased in general among the adolescents who use the internet to play online games, communicate, and utilize social networks. There was no increase in the use of information technologies by adolescents who use the internet for study and live lessons/EBA/distance education purposes. It was found that adolescents meet their need of relatedness and general need satisfaction by using the internet for social networks.